Molecular Cloning of Cellulose Synthase Gene, SpCesA1 from Developing Xylem of Shorea parvifolia spp.parvifolia - Lau, Ee Tiing; Ho, Wei Seng; Azlina, Binti Ahmadi Julaihi (Asian Network for Scientific Information, 2009)
This study reported the isolation and in silico characterization of full-length cellulose synthase (CesA) cDNA from Shorea parvifo/ia spp. parvifolia, an important tropical hardwood tree species- Cellulose synthase (CesA) is a member of processive glycosyltransferases that involved in cellulose biosynthesis of plants, The full-length of SpCesAl cDNA with size 3308 and 3120 bp open reading frames encoding a 1040 amino acid was isolated using RT-PCR and RACE-PCR approaches, The predicted SpCesA} protein contained N-terminal cysteine rich zinc binding domain, 7 putative transmembrane helices (TMH), 4 U-motifs that contain a signature D, D, D; QxxRi•V motif, an alternating conserved region (CR-P) and 2 hypervariåble regions These entire shared domain structures suggest the functional role of SpCesAl is involved in cellulose biosynthesis in secondary vascular tissues of S. parvifolio spp. parvifolia. Sequence comparison also revealed the high similarity (87%) among SpCes,41 and PtrCesA2 of Populus tremuloidesw This further implies the involvement of SpCesA/ in catalyzes the cellulose biosynthesis of secondary cell wall rather than primary cell wall. Thus, identification of new CesA genes from tropical tree genomes is essential for enhancing knowledge Of cellulose biosynthesis in trees that has many fundamental and commercial implications.